Learning how to teach unfamiliar subjects: developing training on writing for publication and presentation of research for health libraries. (3rd April 2020) - Barker, Eleanor; Phillips, Veronica
Abstract: Academic librarians with teaching responsibility have traditionally delivered training in discovering and organising information. However, in recent years, there has been an increased emphasis on supporting researchers through all stages of the research lifecycle. While librarians are ideally placed to provide training in writing for publication and presentation of research, very few in the United Kingdom appear to be doing so. However, there are clear benefits to teaching these subjects. Based on feedback from faculty on user needs, the University of Cambridge Medical Library's training programme was expanded to include training and support in the publication and presentation of research outputs. This article recounts the process by which the new courses were developed, and the techniques used by the library's teaching staff to gain understanding of conventions and requirements of forms of written communication with which they were unfamiliar. It also evaluates the impact of the new courses, discusses next steps and provides advice for other librarians wishing to develop similar courses. D.I.